Bionanotechnology : lessons from nature - Goodsell, David S. (Wiley-Liss, 2013)
"Bionanotechnology: Lessons from Nature shows both students and practitioners how the lessons that may be learned from biology can be applied to nanotechnology today. The first part of the book explores the properties of nanomachines that are available in cells. The second looks to the structure and function of natural nanomachines for guidance in building nanomachinery. The book then concludes with chapters on applications, surveying some of the exciting bionanotechnological tools and techniques that are currently in development, and speculating on those that may prove feasible in the not-too-distant future." "Undergraduates, graduate students, practicing researchers, and policymakers will find David Goodsell's Bionanotechnology an accessible, visually compelling introduction to this exciting field."--BOOK JACKET.